Structural myocardial involvement in adult patients with type 1 myotonic dystrophy - Upinder K. Dhand; Faisal Raja; Kul Aggarwal (MDPI AG, 2013)
Myotonic dystrophy type 1 (DM1) is the commonest muscular dystrophy in adults, affecting multiple organs in addition to skeletal muscles. Cardiac conduction system abnormalities are well recognized as an important component of DM1 phenotype; however, primary structural myocardial abnormalities, which may predispose these patients to congestive heart failure, are not as well characterized. We reviewed the retrospective analysis of the clinical and echocardiographic findings in adult patients with DM1. Among 27 patients (16 male; age 19-61 years) with DM1, the echocardiogram (ECHO) was abnormal in 10 (37%) including one of 6 patients (16%) with congenital myotonic dystrophy. Reduced left ventricular ejection fraction (LVEF ≤50%) was noted in 5, diastolic dysfunction in 4, left atrial dilatation in 3, left ventricular hypertrophy in 2, apical hypokinesia in 1 and mitral valve prolapse in 3 patients. One patient had paradoxical septal movement in the setting of left bundle branch block. Echocardiographic abnormalities significantly correlated with older age; however, patients with systolic dysfunction on echocardiogram ranged in age from 27 to 52 years including 2 patients aged 27 and 34 years. We can conclude that echocardiographic abnormalities are frequent in adult patients with DM1. The incidence is similar in the classical and congenital type of DM1. Overall, echocardiographic abnormalities in DM1 correlate with increasing age; however, reduced LVEF is observed even at young age. Cardiac assessment and monitoring in adult patients with DM1 should include evaluation for primary myocardial involvement.